Chemoenzymatic Total Synthesis of Deoxy‐, epi‐, and Podophyllotoxin and a Biocatalytic Kinetic Resolution of Dibenzylbutyrolactones - Lazzarotto, Mattia (Angew Chem Int Ed Engl, 2019)
Podophyllotoxin is probably the most prominent representative of lignan natural products. Deoxy‐, epi‐, and podophyllotoxin, which are all precursors to frequently used chemotherapeutic agents, were prepared by a stereodivergent biotransformation and a biocatalytic kinetic resolution of the corresponding dibenzylbutyrolactones with the same 2‐oxoglutarate‐dependent dioxygenase. The reaction can be conducted on 2 g scale, and the enzyme allows tailoring of the initial, “natural” structure and thus transforms various non‐natural derivatives. Depending on the substitution pattern, the enzyme performs an oxidative C−C bond formation by C−H activation or hydroxylation at the benzylic position prone to ring closure.